(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Traditionally, public opinion is considered as a specific manifestation and one of the ways of existence of mass consciousness. In public opinion, value judgments (verbal and non-verbal) are expressed, reflecting the attitude of different social groups to the problems, events, facts, phenomena, processes of real reality. And the more these phenomena of reality affect the vital needs, goals, interests of social groups, the more explicit as a rule, public opinion is expressed.